Does inequality reduce mobility? The Great Gatsby Curve and its mechanisms - Gunnar Brandén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
A body of evidence has emerged in the literature on intergenerational mobility documenting that countries with large income differences also have less intergenerational mobility: a relationship known as the Great Gatsby Curve. In this paper, I estimate the Great Gatsby Curve within Sweden exploiting both cross-sectional and longitudinal variation. I find that men who grew up in regions or periods with high levels of income inequality experienced less intergenerational mobility as adults, thereby confirming the existence of a Great Gatsby Curve in Sweden. I also present new evidence on the underlying mechanisms of the Great Gatsby Curve. By decomposing intergenerational mobility into separate transmission channels, I find that the mediating effects that educational attainment and cognitive and non-cognitive skills have on the persistence of socioeconomic status across generations drive the Great Gatsby Curve.
Keywords: D31; I24; J62; R0; 330; Intergenerational mobility; equality of opportunity; inequality